Analysis of mode choice behavior of students of exclusive schools in Metro Manila the case of Ateneo de Manila University and Miriam College - De Guzman, Mark P. (1999)
Trip purpose consequently is one major factor in the worsening traffic problem in Metro Manila. School trips are one of these trip purposes that contribute to it. Many practical transport policy issues that can alleviate traffic congestion are concerned with mode choice. Travel patterns, trip characteristics, socio-economic characteristics, and transport related policies affect mode choice behavior. The mode choice for this study is generally between car and others (public transport) wherein, public transport includes jeepney, tricycle, bus, taxi, FX (HOV), and LRT. Walk is hereby considered as an access mode. Data collection was conducted on July 14, 15, 16, 19 and August 9 of 1999 at Miriam College and Ateneo de Manila University. Target samples were 400 per university. A total of 350 and 170 samples were collected in Miriam College and Ateneo de Manila respectively.
The research is concerned with the development of a linear and non-linear regression models for mode choice. It was found out that majority of them are car users and the variables that affects this choice is car ownership, parking access, and travel time. Travel time is not accurate in the analysis since the distance between the origin and the destination is not included due to time constraints. The choice of car is minimized with the variable Unified Vehicle Volume Reduction Program (UVVRP) effectiveness. This UVVRP effectiveness is only applied on a one-day basis; thus it is not effective in the alleviation of traffic congestion. Moreover, majority of them owns more than two cars so it is possible that car switching is being done when this policy takes into effect on that day. Therefore, an alternative policy is being conducted in this study which is the carpooling as a donor or a passenger. Thus carpooling policies will probably succeed in the alleviation of traffic congestion along the study area.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Choice of transportation